(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This article talks about the advanced foreign experience in the development of technical thinking of students of the academic Lyceum. The author, relying on pedagogical data, analyzed the problem on the basis of existing scientific literature and studied the existing peculiarities of foreign advanced experience in the development of technical thinking of students of the academic Lyceum.